Visualization of mRNA Translation Within Germ Granule Biphasic Organization in Drosophila Early Embryo. - Haidar, A.; Simonelig, M.; Ramat, A. (Bio-protocol, 2025)
Super-resolution imaging of RNA-protein (RNP) condensates has shown that most are composed of different immiscible phases reflected by a heterogenous distribution of their main components. Linking RNA-protein condensate's inner organization with their different functions in mRNA regulation remains a challenge, particularly in multicellular organisms. Drosophila germ granules are a model of RNA-protein condensates known for their role in mRNA storage and localized protein production in the early embryo. Present at the posterior pole of the embryo within a specialized cytoplasm called germplasm, they are composed of maternal mRNAs as well as four main proteins that play a key role in germ granule formation, maintenance, and function. Germ granules are necessary and sufficient to drive germ cell formation through translational regulation of maternal mRNAs such as nanos. Due to their localization at the posterior tip of the ovoid embryo and small size, the classical imaging setup does not provide enough resolution to reach their inner organization. Here, we present a specific mounting design that reduces the distance between the germ granule and the objectives. This method provides optimal resolution for the imaging of germ granules by super-resolution microscopy, allowing us to demonstrate their biphasic organization characterized by the enrichment of the four main proteins in the outermost part of the granule. Furthermore, combined with the direct visualization of nanos mRNA translation using the Suntag approach, this method enables the localization of translation events within the germ granule's inner organization and thus reveals the spatial organization of its functions. This approach reveals how germ granules serve simultaneously as mRNA storage hubs and sites of translation activation during development. This work also highlights the importance of considering condensates' inner organization when investigating their functions. Key features Method for super-resolution imaging of germ granules in Drosophila early embryo. Analysis of RNP condensate functional organization. Simultaneous recording of RNP condensate function and organization.